Studi Fenomenologi Pelecehan Seksual Pada Wanita Melalui Sosial Media - Abdullah, Ahmad Fatihul Amin; wartoyo, Fx; Kurniawan, Agung (Penerbit STKIP PGRI Bangkalan, 2019)
The purpose of this study is to find out the forms of sexual abuse that occur on social media and the response of social media users to sexual harassment. This research is motivated by the increasing prevalence of social media users. Interaction in the virtual world sometimes has a negative impact on its users. This study uses a qualitative approach. Data collection techniques using interviews and observation. Data analysis techniques use discourse analysis. The results of this study obtained data that sexual harassment that occurs on social media is divided into writing harassment, verbal abuse, visual abuse, and real abuse. The response from women who use social media is that most of them regret the existence of sexual harassment activities